Heterojunction Solar Cells Based on Silicon and Composite Films of Graphene Oxide and Carbon Nanotubes. Issue 17 (8th May 2015) - Yu, LePing; Tune, Daniel; Shearer, Cameron; Shapter, Joseph
Abstract Graphene oxide (GO) sheets have been used as the surfactant to disperse single‐walled carbon nanotubes (CNT) in water to prepare GO/CNT electrodes that are applied to silicon to form a heterojunction that can be used in solar cells. GO/CNT films with different ratios of the two components and with various thicknesses have been used as semitransparent electrodes, and the influence of both factors on the performance of the solar cell has been studied. The degradation rate of the GO/CNT‐silicon devices under ambient conditions has also been explored. The influence of the film thickness on the device performance is related to the interplay of two competing factors, namely, sheet resistance and transmittance. CNTs help to improve the conductivity of the GO/CNT film, and GO is able to protect the silicon from oxidation in the atmosphere.